2021
DOI: 10.1093/jee/toab123
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Effects of the Microbial-Derived Insecticide Spinetoram on the Growth and Fecundity of the Fall Armyworm (Lepidoptera: Noctuidae)

Abstract: The fall armyworm, Spodoptera frugiperda (J. E. Smith), is one of the most important pests in tropical and subtropical regions of American. S. frugiperda was first detected in Southern China in January 2019, and then subsequently invaded in 26 provinces. Spinetoram widely used for pest management is recommended for S. frugiperda control. The sublethal effects of spinetoram on S. frugiperda were investigated in the present study. The toxicity of spinetoram against S. frugiperda larvae was determined after one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The fitness and population life tables of S. frugiperda on solanaceous and oilseed crops have been determined in earlier studies [ 48 , 49 ]. Using a two-sex life table, sub-lethal effects of spinetroam against S. frugiperda growth and fecundity were determined [ 50 ]. Similarly, Iqbal et al [ 51 ] used an age-stage, two-sex life table to investigate the impact that zinc oxide generated in the culture supernatant of B. thuringiensis had on the demographic characteristics of Musca domestica .…”
Section: Introductionmentioning
confidence: 99%
“…The fitness and population life tables of S. frugiperda on solanaceous and oilseed crops have been determined in earlier studies [ 48 , 49 ]. Using a two-sex life table, sub-lethal effects of spinetroam against S. frugiperda growth and fecundity were determined [ 50 ]. Similarly, Iqbal et al [ 51 ] used an age-stage, two-sex life table to investigate the impact that zinc oxide generated in the culture supernatant of B. thuringiensis had on the demographic characteristics of Musca domestica .…”
Section: Introductionmentioning
confidence: 99%
“…In order to conduct the emergency prevention system against FAW, the application of EMB recommended by MARA may not only cause direct FAW larval mortality but also indirectly negatively lead to sublethal effects [18]. However, information on the sublethal effects of EMB on FAW is little [36]. The results of the present study showed that even a low dose of EMB could influence the performance of FAW parental and offspring generations.…”
Section: Discussionmentioning
confidence: 60%
“…The high efficacy of spinetoram had previously been reported in various Lepidopteran pests [9][10][11][12][13][14]. Most studies also reported that more than 50% of larvae died in the first three days after exposure.…”
Section: Resultsmentioning
confidence: 92%